CSR and Stakeholder Theory: A Tale of Adam Smith - Brown, Jill A. (Journal of business ethics, 2013)
This article leverages insights from the body of Adam Smith’s work, including two lesser-known manuscripts—the Theory of Moral Sentiments and Lectures in Jurisprudence—to help answer the question as to how companies should morally prioritize corporate social responsibility (CSR) initiatives and stakeholder claims. Smith makes philosophical distinctions between justice and beneficence and perfect and imperfect rights, and we leverage those distinctions to speak to contemporary CSR and stakeholder management theories. We address the often-neglected question as to how far a company should be expected to go in pursuit of CSR initiatives and we offer a fresh perspective as to the role of business in relation to stakeholders and to society as a whole. Smith’s moral insights help us to propose a practical framework of legitimacy in stakeholder claims that can help managers select appropriate and responsible CSR activities.